Perinatal outcome of babies born to mothers with antepartum eclampsia: A study from tertiary care hospital of Central India - Sahu, Priyanka; Goyal, Prachi; Mehta, Nirbhay; Bhattacharjee, Somen (Asian Journal of Medical Sciences, 2022)
Background: Eclampsia is a major cause of perinatal mortality. There is a need for studies that will correlate maternal factors and perinatal outcome, which will provide potential strategies to improve fetal outcomes in pregnancies complicated by eclampsia. Aims and Objectives: This study aims to study perinatal outcome of babies born to mothers with antepartum eclampsia and to correlate outcomes with convulsion delivery interval. Materials and Methods: A study included 200 patients diagnosed and managed as antepartum eclampsia in the Department of Obstetrics and Gynaecology in MGM Medical College, Indore. A detailed pro forma was prepared and was filled with patient’s information, investigations, treatment, and birth details. The final outcome of both, the mother and her newborn, including stillbirths and early neonatal deaths was included in the study and the perinatal outcome was correlated with convulsion delivery interval. Results: Incidence of antepartum eclampsia in our study was 2.1%. About 86.4% of women lack regular antenatal care at health care center. Only 7% of women delivered within 6 h of onset of convulsion. Case fatality rate was found to be 13%. There were 59.5% premature deliveries. Perinatal mortality (stillbirth and early neonatal deaths) was 42.5%. Significant association was found between convulsion delivery interval and perinatal outcome (P<0.05). Furthermore, association between use of multiple antiepileptic agents and perinatal outcomes was statistically significant. Conclusion: Eclampsia being a major cause of perinatal mortality need early diagnosis, prompt referral from peripheral health centers, and timely intervention for improvising both perinatal and maternal outcomes.